To simplify the expression \( - (2x + 6)(3x + 4) + 5x^2 - 7x \), we can follow these steps:
-
Distribute:
\[ (2x + 6)(3x + 4) = 2x \cdot 3x + 2x \cdot 4 + 6 \cdot 3x + 6 \cdot 4 \]
\[ = 6x^2 + 8x + 18x + 24 = 6x^2 + 26x + 24 \]
-
Negate it:
\[
- (6x^2 + 26x + 24) = -6x^2 - 26x - 24 \]
-
Combine with the rest of the expression:
Now add \( 5x^2 - 7x \):
\[ -6x^2 - 26x - 24 + 5x^2 - 7x \]
Combine like terms:
\[ (-6x^2 + 5x^2) + (-26x - 7x) - 24 \]
\[ = -1x^2 - 33x - 24 \]
-
Final result:
Thus, the simplified expression is:
\[-x^2 - 33x - 24\]
So the correct response is:
\(-x^2 - 33x - 24\) (negative x squared minus 33 x minus 24).